2018
DOI: 10.1038/s41467-018-07340-5
|View full text |Cite
|
Sign up to set email alerts
|

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes

Abstract: Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 33 publications
5
126
2
Order By: Relevance
“…In the previously reported loci, on Chr5 there is only one SNP, rs758080886, which reaches GWAS-significant evidence for association with IMTmean which is located 3417b from the previously reported lead SNP rs224904 6 . rs758080886 is not available in the reference panel used by LocusZoom 15 and is therefore not plotted, hence this region is represented by the previously reported SNP, rs224904.…”
Section: Phenotypingmentioning
confidence: 65%
See 2 more Smart Citations
“…In the previously reported loci, on Chr5 there is only one SNP, rs758080886, which reaches GWAS-significant evidence for association with IMTmean which is located 3417b from the previously reported lead SNP rs224904 6 . rs758080886 is not available in the reference panel used by LocusZoom 15 and is therefore not plotted, hence this region is represented by the previously reported SNP, rs224904.…”
Section: Phenotypingmentioning
confidence: 65%
“…The single largest study within the metaanalysis included 8,663 individuals (approximately evenly split between men and women. That meta-analysis reported 11 robustly associated loci 6 , of which nine lead SNPs were available in UKB (Stable 2). Seven of these demonstrated significant (p<0.05) associations with IMTmean, with consistent effect directions when compared to the previous report 6 (Stable 2).…”
Section: Ukb Imt Gwas and The Charge Consortium Imt Gwas Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, cIMT and carotid plaque may represent distinct phenotypes of vascular remodelling . This theory is underpinned by genetic studies that revealed distinct genes to be associated with cIMT and carotid plaque . On the other hand, cIMT and carotid plaque are considered to represent different stages of atherogenesis characterised by continuous arterial wall growth.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This theory is underpinned by genetic studies that revealed distinct genes to be associated with cIMT and carotid plaque. 17,18 On the other hand, cIMT and carotid plaque are considered to represent different stages of atherogenesis characterised by continuous arterial wall growth. Following this theory would imply cIMT being a predictive measure for the initiation and development of new carotid plaque and would further endorse the relevance of cIMT as a tool to quantify atherosclerosis-and identify individuals at elevated risk for future CVD-at a very early stage.…”
Section: Introductionmentioning
confidence: 99%